PENGARUH FERMENTASI ISI RUMEN SAPI DENGAN Trichoderma viride TERHADAP ENERGI METABOLIS PADA AYAM BROILER - Rarumangkay, Jeni (Universitas Sam Ratulangi, 2015)
Â THE EFFECT OF DRIED COW RUMEN FERMENTATION WITH TRICHODERMA VIRIDE ON METABOLIZABLE ENERGY VALUE OF BROILER. The purpose of this experiment was to determine the metabolizable energy of dried cow rumen. The experiment use dried cow rumen and dried cow rumen fermented Trichoderma viride during 9 days with 0,3% inoculum dose. The experiment use 18 six weeks old male broiler metabolizable energy parameter were analyzed with Wilcoxon test. The result of this experiment showed fermentation with Trichoderma viride could increase the metabolizable energy of dried cow rumen. Â Key word : Fermentation of dried cow rumen, broiler, metabolizable energy